2001
DOI: 10.1128/jb.183.21.6265-6273.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Sequencing, and Characterization of the Iturin A Operon

Abstract: Bacillus subtilis RB14 is a producer of the antifungal lipopeptide iturin A. Using a transposon, we identified and cloned the iturin A synthetase operon of RB14, and the sequence of this operon was also determined. The iturin A operon spans a region that is more than 38 kb long and is composed of four open reading frames, ituD, ituA, ituB, and ituC. The ituD gene encodes a putative malonyl coenzyme A transacylase, whose disruption results in a specific deficiency in iturin A production. The second gene, ituA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
189
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(192 citation statements)
references
References 44 publications
(46 reference statements)
0
189
2
1
Order By: Relevance
“…This is not consistent with other studies using Tn917 for iturin and fengycin biosynthesis genes (40,41). In those studies, the transposon disrupted the nonribosomal peptide synthetase genes and blocked the antimicrobial peptide synthesis completely.…”
Section: Discussioncontrasting
confidence: 49%
“…This is not consistent with other studies using Tn917 for iturin and fengycin biosynthesis genes (40,41). In those studies, the transposon disrupted the nonribosomal peptide synthetase genes and blocked the antimicrobial peptide synthesis completely.…”
Section: Discussioncontrasting
confidence: 49%
“…according to the amino acid activated) (Challis et al, 2000). For Bacillus subtilis it has been proposed that LGT of large NRPS gene clusters between strains is responsible for the very similar gene clusters present (Tsuge et al, 2001). Investigating the sequence variation in mcy genes of various Microcystis strains, Mikalsen et al (2003) suggested that frequent recombinations between imperfect repeats (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus amyloliquefaciens is closely related to B. subtilis of which several strains have been reported to be effective in the control of plant pathogens (Asaka and Shoda 1996;Yoshida et al 2001;Yu et al 2002) with the production of antibiotics in the lipopeptide family (Yu et al 2002;Koumoutsi et alAntibiotics in the family iturin, represented by iturin A, mycosubtilin and bacillomycin are most commonly studied for their biocontrol activity. These are heptapeptides with a b-amino fatty acid that exhibit strong antifungal activity (Thimon et al 1995;Duitman et al 1999;Tsuge et al 2001;Moyne et al 2004). Iturin A specifically shows a strong antibiotic activity with a broad antifungal spectrum, making it an ideal potential biological control agent with the aim of reducing the use of chemical pesticides in agriculture (Hsieh et al 2008).…”
Section: Introductionmentioning
confidence: 99%